Artesunate prevents rats from the clozapine-induced hepatic steatosis and elevation in plasma triglycerides - Li Y (Dove Medical Press, 2017)
Yanmei Li,1,2 Ruibing Su,3 Shuqin Xu,2 Qingjun Huang,1 Haiyun Xu1,2 1The Mental Health Center, Shantou University Medical College, Shantou, Guangdong Province, People’s Republic of China; 2Department of Anatomy, Shantou University Medical College, Shantou, Guangdong Province, People’s Republic of China; 3Department of Forensics and Pathology, Shantou University Medical College, Shantou, Guangdong Province, People’s Republic of China Abstract: Clozapine is an atypical antipsychotic with therapeutic efficacy in treatment-resistant schizophrenia patients and low incidence of extrapyramidal side effects. However, the use of clozapine has been limited by its adverse effects on metabolism. Artesunate is a semisynthetic derivative of artemisinin and was shown to decrease the plasma cholesterol and triglyceride in rabbits and rats in recent studies. The aim of this study was to examine possible effects of artesunate on the clozapine-induced metabolic alterations in rats given saline, clozapine, artesunate, or clozapine plus artesunate for 6 weeks. The clozapine group showed significantly high plasma levels of triglyceride, hepatic steatosis, and fibrosis along with high levels of C-reactive protein, alanine aminotransferase, and aspartate aminotransferase compared to the saline group. But the treatment had no effect on weight gain and caused no hyperglycemia, hyperinsulinemia, and behavioral changes in the rats. More significantly, these clozapine-induced changes were not seen in rats coadministered with clozapine plus artesunate. These results added evidence supporting psychiatrists to try add-on treatment of artesunate in schizophrenia patients to ameliorate clozapine-induced adverse metabolic effects. Keywords: artesunate, clozapine, dyslipidemia, hepatic steatosis, schizophrenia